Are There Stable Factors in Preadolescent Girls’ Externalizing Behaviors? - Loeber, Rolf; Pardini, Dustin A.; Hipwell, Alison; Stouthamer-Loeber, Magda; Keenan, Kate; Sembower, Mark A. (Journal of abnormal child psychology, 2009)
Relatively little is known about the factor structure of disruptive behavior among preadolescent girls. The present study reports on exploratory and confirmatory factor analyses of disruptive girl behavior over four successive data waves as rated by parents and teachers in a large, representative community sample of girls ( N = 2,451). Five factors were identified from parent ratings (oppositional behavior/conduct problems, inattention, hyperactivity/impulsivity, relational aggression, and callous-unemotional behaviors), and four factors were identified derived from teacher ratings (oppositional behavior/conduct problems/callous-unemotional behaviors, inattention, hyperactivityimpulsivity, and relational aggression). There was a high degree of consistency of items loading on equivalent factors across parent and teacher ratings. Year-to-year stability of factors between ages five and 12 was high for parent ratings (ICC = 0.70 to 0.88), and slightly lower for teacher ratings (ICC = 0.56 to 0.83). These findings are discussed in terms of possible adjustment to the criteria for children's disruptive behavior disorders found in the Diagnostic and Statistical Manual for Mental Disorders.